PENGARUH MODEL PENDEKATAN TAKTIS TERHADAP KETERAMPILAN BERMAIN BOLA VOLI PADA SISWA KELAS XI SMA NEGERI 6 KARAWANG BARAT - Azis, Ghofar; Mahardhika, Dhika Bayu; Yuda, Aria Kusuma (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of the tactical approach model on volleyball playing skills. This research uses quantitative descriptive method with pre-experimental design method with one group pretest-postest. The population of this study consisted of class XI students of SMA Negeri 6 Karawang, totaling 250 people with research sampling using random sampling techniques totaling 38 people. Data collection techniques using the volleyball game performance assessment instrument skills test. The data analysis process uses the IBM SPSS Statistics version 26 application, and includes descriptive statistical tests, normality tests, homogeneity tests, and hypothesis testing. The results of the study were described using descriptive statistical data analysis with pretest values average mean = 40.58, median = 40.00, mode 38, standard deviation 3.500, variance 6.250, minimum 36, maximum 45. While the results of descriptive statistical analysis with posttest values average mean = 42.68, median = 42.00, mode 40, standard deviation 3.264, variance 10.654, minimum 38, maximum 50. Based on paired sample t-test obtained significance value = 0.003 sig value. (2-tailed) < 0.05, then H₀ is rejected and Hₐ is accepted, because the calculated t value is 3.218 > 2.026. The conclusion of this study is that learning by using a tactical approach model can affect volleyball skills.